State and Trends of Sustainable Development of Tourism in Ukraine and the World - SHCHERBAKOVA, Nadiia A. (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
Nowadays, tourism is among the most important socio-economic sectors of the world economy, so the urgency of the problem under investigation is due to the need for sustainable development of tourism in Ukraine. The purpose of the article is to develop recommendations for the sustainable development of tourism in the world and in Ukraine, in particular, in the Carpathian region. To the leading methods of research problems of the article include the analysis of theoretical sources, analysis of statistical data, comparison. The article examined the essence of tourism, its categories, nature and factors of sustainable tourism development, studied the development trends of tourism in the world, analyzed the development of tourism in Ukraine and the Carpathian region, made the comparison of the indicators of tourism development in Ukraine and in other countries, identified problems of sustainable tourism development in Ukraine, ways of their decision are developed. The materials of the article have practical value for ensuring the sustainable development of tourism in Ukraine, in the Carpathian region or at the level of other regions of the country.